Endovascular treatments, predictors and outcomes of cerebral aneurysm - Daniel Encarnación Santos; Gennady Chmutin; Ahmad Rami Kassar; Aysi Gordon Gullanyi; Ismail Bozkurt; Jack Wellignton; Bipin Chaurasia (Romanian Neurosurgery)
Background: Recent studies in surgical techniques have significantly transformed therapeutic approaches, leading to substantial decreases in morbidity and mortality rates. Differential diagnosis plays a pivotal role in determining the most suitable surgical strategies for addressing aneurysms. Historically, clipping has been considered a longstanding tradition in the vascular field between 1937 and 1975, pioneered by Microneurosurgery pioneers Yasargil and Fox.